Réponses

Meilleure réponse !
2014-05-21T13:50:29+02:00
58) a) 10 puissance 3 * 10 puissance 4 /  10 puissance 2
= 10 puissance 3+4 / 10 puissance 2
= 10 puissance 7 / 10 puissance 2
= 10 puissance 7-2
= 10 puissance 5

b) 10 puissance 5 *10 puissance 3 / 10 puissance -2
= 10 puissance 5+3 / 10 puissance -2
= 10 puissance 8 / 10 puissance -2
= 10 puissance 8+2
= 10 puissance 10

c) 10 puissance 2* 10 puissance -6 / 10 puissance 3* 10 puissance -5
= 10 puissance 2-6 / 10 puissance 3-5
= 10 puissance -8 / 10 puissance -8
= 10 puissance -8+8
= 10 puissance 0

62) a) ( 10 puissance 2) puissance 4
= 10 puissance 2*4
= 10 puissance 8

b) (10 puissance 3) puissance 2
= 10 puissance 3*2
= 10 puissance 6

c) (10 puissance 4) puissance 5
= 10 puissance 4*5
= 10 puissance 20

d) (10 puissance 3) puissance -2
= 10 puissance 3*(-2)
= 10 puissance -6

e) 10 puissance 5* (10 puissance 2) puissance 3
= 10 puissance 5* 10 puissance 2*3
= 10 puissance 5*10 puissance 6
= 10 puissance 5+6
= 10 puissance 11

f) 10 puissance -8*(10 puissance 3) puissance 2
= 10 puissance -8* 10 puissance 3*2
= 10 puissance -8* 10 puissance 6
= 10 puissance -8+6
= 10 puissance -2

LE SIGNE * VEUT DIRE FOIS (MULTIPLIER)